Balanço hídrico em povoamento de eucalipto com diferentes densidades de plantas em argissolo - Consensa, Claudine Ohana Barcellos (2015)
Eucalyptus plantations have increased significantly in recent times, but the productivity of forests are very sensitive to the availability of natural resources such as water, nutrients and light. In order to assess the water dynamics and characterize water flows in soil in a eucalyptus plantation in replacement of native grassland, there was a study in the city of São Francisco de Assis, RS, located in the “Bioma Pampa. Different densities were evaluated: 3,5x3,5m; 3,5x1,75m; 1,75x1,75m and 1,75x0,75m. The overall distribution of rainfall internal precipitation, straining the trunk interception losses of the canopy the and soil volumetric water content were evaluated during a period of one year. Three pluviometers were installed in the field area to measure and collect global precipitation. To measure the internal precipitation, 36 pluviometers were installed inside the plantation and 36 collectors were used (in selected trees) to determine the stemflow. The soil volumetric water content was monitored continuously to a depth of 2.10 m, using an automated TDR. The evapotranspiration was determined by the water balance equation, using the mass conservation method. The relationship between the biomass increase and the water amount transpired in different planting spacing, allow estimating the efficiency of water use by eucalyptus trees. The effective rainfall is higher in a narrower spacing plant, due to the increased water intake by stemflow, which results in lower treetop interception. The interception rate is lower in higher rainfall and decreases with increasing density of trees in the settement. The average evapotranspiration ranged from 4.0 to 4.5 mm day-1, with similar values among different planting spacings and is reduced in low-rainfall periods. There were no adverse effects on water resources and soil water regime due to the eucalyptus replacing natural herbaceous vegetation reforestation in Pampa Biome, evidenced by the soil water content that never was less than the value of permanent wilting point (1.5MPa). The water efficient use of Eucalyptus dunnii with 6 years old in the “Pampa biome” region varies from 3.27 to 2.40 g L-1.